A quantitative study on the influence of breadth of open innovation on SMEs product-service performance: The moderating effect of type of innovation - Idika Awa Uduma; Andy Fred Wali; Len Tiu Wright (Cogent Business & Management, 2015)
The study investigates the influence of breadth of open innovation strategy on product and service performance of UK SMEs and how the relationship is affected by the type of innovation. The respondents were 72 senior employees randomly sampled from SMEs in UK manufacturing sector. We collected primary data using survey questionnaire. Multiple regression technique through Statistical Package for Social Sciences (SPSS) version 21 was used to analyse the data. We found that breadth of open innovation have curvilinear relationship to both incremental and radical product performance. Also, results showed that incremental as well as radical innovation moderates the influence of breadth of open innovation on the product performance. We concluded that adoption of optimum breadth of open innovation strategy supports SMEs' product-service performance. We recommended that SMEs' policy-makers should adopt a balanced breadth of open innovation strategy in order to foster the achievement of their product performance goals, depending on the particular type of innovation they intend to achieve.
Keywords: 650